Phosphonated nanocelluloses from sequential oxidative–reductive treatment—Physicochemical characteristics and thermal properties. (20th November 2015) - Sirviö, Juho Antti; Hasa, Tapani; Ahola, Juha; Liimatainen, Henrikki; Niinimäki, Jouko; Hormi, Osmo
Highlights: Phosphonated nanocelluloses were obtained by a sequential oxidative–reductive treatment. A low oxidation degree resulted in the production of long nanofibrillated cellulose. A higher oxidation degree produced short nanocrystalline cellulose. High charring properties were obtained even with a low degree of substitution. Abstract: Nanocellulosic materials with good thermal stability are highly desirable for applications, such as reinforcement and filler agents in composites. In the present work, phosphonated cellulose was utilized to obtain nanocelluloses with good thermal stability and potential intumescent properties. Phosphonated cellulose was synthetized from birch pulp via sequential periodate oxidation and reductive amination using a bisphosphonate group-containing amine, sodium alendronate, as a phosphonating reagent. After high-pressure homogenization, bisphosphonate cellulose nanofibres or nanocrystals were obtained, depending on the initial oxidation degree. Nanofibres had a typical diameter of 3.8 nm and length of several micrometers, whereas nanocrystals exhibited a width of about 6 nm and an average length of 103–129 nm. All nanocelluloses exhibited cellulose I crystalline structures and high transparency in water solutions. Phosphonated nanocelluloses exhibited good thermal stability and a greater amount of residual char was formed at 700 °C compared to birch pulp and mechanically produced, non-chemically modified NFC.